Tactile stimulation reduces fear in fish - Schirmer, Annett; Jesuthasan, Suresh J.; Mathuru, Ajay (Frontiers in Behavioral Neuroscience, 2013)
Being groomed or touched can counter stress and negative affect in mammals. In two experiments we explored whether a similar phenomenon exists in non-mammals like zebrafish. In Experiment 1, we exposed zebrafish to a natural stressor, a chemical alarm signal released by injured conspecifics. Before moving them into an observation tank, one group of fish was washed and then subjected to a water current that served as the tactile stimulus. The other group was simply washed. Fish with tactile treatment demonstrated fewer fear behaviors (e.g., bottom dwelling) and lower cortisol levels than fish without. In Experiment 2, we ascertained a role of somatosensation in these effects. Using a similar paradigm as in Experiment 1, we recorded fear behaviors of intact fish and fish with damaged lateral line hair cells. Relative to the former, the latter benefited less from the tactile stimulus during fear recovery. Together these findings show that tactile stimulation can calm fish and that tactile receptors, evolutionarily older than those present in mammals, contribute to this phenomenon.